2020
DOI: 10.1029/2019jb018105
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Displacements of the Amazon Basin From GRACE and GPS

Abstract: The extent to which Gravity Recovery and Climate Experiment (GRACE)‐recovered gravity anomalies can improve our understanding of Global Positioning System (GPS)‐measured vertical displacements is currently uncertain. To address this issue, we compared vertical displacements measured by 23 GPS stations in the Amazon basin with displacements estimated from GRACE geopotential fields. We show that despite poor correlation ( r2=0.15) between rate estimates in GPS and GRACE‐derived displacement time series, further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
2
11
2
Order By: Relevance
“…This may explain why when considering overall trends Knowles et al. (2020) found an uplift trend in the Amazon, while our results show a combination of uplift and subsidence. This is consistent with the imaged temporal variability and indicates that the trends in the Amazon Basin are likely not permanent features of the vertical GPS rate field, and the sign of uplift depends on the time period of observation.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…This may explain why when considering overall trends Knowles et al. (2020) found an uplift trend in the Amazon, while our results show a combination of uplift and subsidence. This is consistent with the imaged temporal variability and indicates that the trends in the Amazon Basin are likely not permanent features of the vertical GPS rate field, and the sign of uplift depends on the time period of observation.…”
Section: Resultscontrasting
confidence: 55%
“…This indicates that changes in rates in the Amazon are not only seasonal but also have trends that inflect upward and downward, changing sign on multi-annual time scales between drought and wet periods. This may explain why when considering overall trends Knowles et al, (2020) found an uplift trend in the Amazon, while our results show a combination of uplift and subsidence. This is consistent with the imaged temporal variability and indicates that the trends in the Amazon Basin are likely not permanent features of the vertical GPS rate field, and the sign of uplift depends on the time period of observation.…”
Section: The Amazon Basincontrasting
confidence: 50%
“…Previous studies analyzed the loading signal in South America using space geodesy time series. It has been demonstrated that GRACE signal is consistent with in situ water level and discharge data [31] and that GRACE and GPS give complementary estimates of vertical displacement in the Amazon basin [32]. The observed displacement includes seasonal, interannual and secular variations in mass loading.…”
Section: Introductionmentioning
confidence: 61%
“…Despite the GRACE hydrological signal being dominated by seasonal and long-term variability, recent changes in terrestrial water storage in South American river basins have been evidenced [33]. In particular it concerns drought in 2010 in the Amazon area, in 2012-2014 in the Sao Paulo region [34] or the 2015-2016 severe drought, as well as extreme floods in 2011-2012 and 2013-2014 [32]. GPS time series analysis is also useful to monitor hydrological hazard, as it was performed on the vertical loading signal induced by drought in Brazil [35].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors demonstrated the usefulness of GRACE satellite mission data for investigating temporal variations of geoid/quasigeoid heights, e.g., [13][14][15][16][17][18][19]. Moreover, many authors have proved that the estimated vertical deformations of the Earth's surface using GRACE satellite mission data are in a good agreement with the corresponding ones determined from other space geodetic techniques such as GNSS on a global scale, e.g., [20][21][22], on a continental scale, e.g., [23,24] in Europe, as well as on a local/regional scale, e.g., [25,26] in the Amazon basin, [27] in the West Africa, [28] in the East Africa, [29] in Japan, [30] in Bangladesh, [31][32][33] in China, [34,35] in Tibet, [36,37] in Poland, [38] in Greenland, and [39][40][41][42] in the North America, and Very Long Baseline Interferometry (VLBI) (e.g., [43]). The use of GRACE satellite mission data for estimating physical height changes, i.e., temporal variations of orthometric/normal heights, was investigated on local and regional scales for the area of Turkey, Poland, Central Europe and Greenland [7][8][9][10]44].…”
Section: Introductionmentioning
confidence: 92%